Elementary school class. - Unknown:::Creator::::::::::::; Flaherty, John Melvin (collector):::Contributor::::::::::::
Photograph shows an elementary classroom at Santa Anita, California Assembly Center. The children are all using the "Elson Readers, Book 2" as their textbook.